Production of Free Radicals by Mitochondria: A Biochemistry Approach - Usman Garba Kurmi; Fatima Abubakar; Ruqayya Ali Uthman; Isah Adamu Baushe; Hadiza Abubakar Balkore; Khadija Muhammad; Prosper Obed Chukwuemeka (International Journal of Community Service & Engagement, 2020)
The production of superoxide by mitochondria strongly depends on the mitochondrial respiratory chain. It is believed that the acetylation of cytochrome c prevents its reoxidation by mitochondrial cytochrome oxidase and direct reduction by NADH-or succinate-dependent cytochrome c reductase. It is believed that ubiquinone can be one of the major producers of superoxide because the depletion of endogenous ubiquinone resulted in the formation of diminishing hydrogen peroxide.